2007
DOI: 10.1155/2007/14983
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator Activated Receptor Ligands as Regulators of Airway Inflammation and Remodelling in Chronic Lung Disease

Abstract: Inflammation is a major component in the pathology of chronic lung diseases, including asthma. Anti-inflammatory treatment with corticosteroids is not effective in all patients. Thus, new therapeutic options are required to control diverse cellular functions that are currently not optimally targeted by these drugs in order to inhibit inflammation and its sequelae in lung disease. Peroxisome proliferator activated receptors (PPARs), originally characterised as regulators of lipid and glucose metabolism, offer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 90 publications
2
47
0
Order By: Relevance
“…PPARg is a widely expressed ligandactivated transcription factor implicated in human lung diseases associated with inflammation and remodeling (10,14). PPARg is the target for the thiazolidinedione class of synthetic antidiabetic agents, including RGZ (39), PGZ, and CGZ as well as the proposed endogenous agonist 15 d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPARg is a widely expressed ligandactivated transcription factor implicated in human lung diseases associated with inflammation and remodeling (10,14). PPARg is the target for the thiazolidinedione class of synthetic antidiabetic agents, including RGZ (39), PGZ, and CGZ as well as the proposed endogenous agonist 15 d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%
“…RGZ and ciglitazone (CGZ) regulate ASMC proliferation and the production of inflammatory mediators such as GM-CSF in vitro (10). Consistent with these actions, chronic treatment with PPARg agonists inhibits inflammatory cell influx, airway wall remodeling, and the development of airways hyperresponsiveness to the bronchoconstrictor methacholine (MCh) in mice with ovalbumin-induced airway disease (11)(12)(13)(14)(15) (reviewed in Reference 10).…”
mentioning
confidence: 96%
“…As in the present study, Voelkel and colleagues found little PPARg staining in the medial layer of normal lungs or in the proliferating cells of plexiform lesions, but they did not examine PPARg expression in the pulmonary smooth muscle of patients with IPAH (13). The consequence of elevated PPARg expression within the medial layer and its impact on disease progression warrants further investigation to determine whether increased expression translates into enhanced PPARg activity or responsiveness to endogenous ligand activators, such as the prostaglandin metabolite 5-deoxy-delta-12,14-prostaglandin J 2 (10). The overlapping concentration-response curves to the antiproliferative effects of the PPARg agonist rosiglitazone we observed in PASMCs from normal and IPAH cells suggests not.…”
Section: Role Of Pparg In Ipahmentioning
confidence: 99%
“…The mechanism of this potentiation is unknown. Treprostinil and rosiglitazone can interact with the ligand-binding domain of PPARg (10,11), so that one agent could enhance the binding of the other ligand activator, thus allowing PPARg to activate at lower agonist concentrations. PPARg also contains many phosphorylation sites (32), so that prostacyclin analogs may modulate PPARg agonist activity in that way.…”
Section: Role Of Pparg In Ipahmentioning
confidence: 99%
See 1 more Smart Citation